Relação experimental entre o raio de curvatura natural do cavaco e os principais parâmetros de usinagem - Sales, Wisley Falco (1999)
A betwween relationship Chip curling and the main cutting parameters was experimentaly determined. The parameters considered were cutting speed, feed rate, depth of cut and rake angle. Orthogonal cutting of ABNT 1020 and ABNT 5140 steels was performed and recorded with a VHS camera and the chip curling was determined using a image analyser. A third degree polinomial function was adjusted for the set of points encountered and the ranking of the influence of the parameters was found by using the Sensibility Adjust Technique. In decreasing order for the ABNT 1020 Steel the ranking was: depth of cut, feed rate, rake angle and cutting speed. For the ABNT 5140 steel the ranking was: depth of cut, rake angle, feed rate and cutting speed.